Respostas
respondido por:
11
X²+9x+x+9=0
X²+10x+9=0
Δ=B²-4.a.c
10²-4.1.9
100-36
Δ=64
-b+-√Δ/2.a
-10+-8/2
X'=-10+8/2 X=-2/2 x'=-1
X''=-10-8/2 = -18/2 = -9
Espero ter ajudado
X²+10x+9=0
Δ=B²-4.a.c
10²-4.1.9
100-36
Δ=64
-b+-√Δ/2.a
-10+-8/2
X'=-10+8/2 X=-2/2 x'=-1
X''=-10-8/2 = -18/2 = -9
Espero ter ajudado
respondido por:
1
x(x+9)+(x+9)=0
x(x+9)+x+9=0
x(x+9)=x=-9
x²+x*9+x=-9
x²+9x+x=-9
x²+10x=-9
x=-10+-10²-4*1*9/2*1
x=-10+-8/2
x=-10+8/2
x=-10-8/2
x= -1
x= -9
x(x+9)+x+9=0
x(x+9)=x=-9
x²+x*9+x=-9
x²+9x+x=-9
x²+10x=-9
x=-10+-10²-4*1*9/2*1
x=-10+-8/2
x=-10+8/2
x=-10-8/2
x= -1
x= -9
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás